Public Procurement Efficiency as Perceived by Market Participants: The Case of Russia. Issue 16 (10th December 2022) - Balaeva, Olga; Rodionova, Yuliya; Yakovlev, Andrei; Tkachenko, Andrey
ABSTRACT: This paper studies the indicators of public procurement efficiency as perceived by procurers and suppliers and what barriers must be overcome to consider procurement efficient. The authors used an online survey of Russian procurers and suppliers conducted in 2020 as the main data source. Methods based on comparison of descriptive statistics and distributions of answers for different subsamples were exploited. The analysis reveals that, despite the importance of fighting corruption and increasing competition, most participants consider the supply of high-quality goods and timely contract execution the most important criteria. COVID-19 has mitigated the rigidity of the regulation but exacerbated the ambiguity problem. During the pandemic, contract execution worsened. To improve procurement efficiency, the regulator should clearly specify requirements and consider the main participants' interests.